Memahami Makna dan Tanda dalam Objek Visual Arsitektur Ruang Publik - Tendy Y. Ramadin; Deddy Mulyana (LP2M ISBI Bandung, 2012)
This brief study focuses on proxemic study approach for public spaces which brushed the reflec- tion of aspiration and collaboration of the artists, designers and their public as phenomenon on the spirit of today (zeitgeist). The study also reads the environmental effect on peopleâ€™s habitude and its surroundings.The study is intended to obtain facts about objects on public spaces ever-evolved, e.g. Cihampelas Avenue Bandung, to identify recent problems and practices implied on tendency of using visual sign as allure. It is also intended to compile ideas about visual signs through relevant proxemic study approach, so that it could be processed into temporary conclusion to advice entrepreneurs, local au- thorities, academics and commoners.Keywords: public space, architecture, visual signs, communication science, proxemic approachÂ Â